Colorectal Cancer in Ulcerative Colitis: Effect of Cancer Prevention Strategy on Survival - A. K. GÜRBÜZ; F. M. GIARDIELLO; T. M. BAYLESS; Steven N. GOODMAN; John H. YARDLEY (Turkish Journal of Gastroenterology, 2020)
-